THE ROLE OF LEADERSHIP STYLE IN CREATING EFFECTIVE WORKING RELATIONSHIPS IN HILIBADALU VILLAGE - Meiman Hidayat Waruwu; Intan Permata Hati Hulu (LPPM YPITI, 2026)
This study aims to analyze the role of leadership style in creating effective working relationships in Hilibadalu Village. The study used a qualitative approach with descriptive methods. Research informants consisted of the village head, village officials, and community leaders selected using purposive sampling. Data collection techniques were carried out through in-depth interviews, observation, and documentation. Data analysis used the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. Data validity was maintained through triangulation of sources and techniques. The results showed that a leadership style that tends to be authoritarian, less communicative, and often blames subordinates has a negative impact on working relationships. This condition is characterized by closed communication, low trust, and weak cooperation between village officials. This study concluded that the implementation of a more democratic and participatory leadership style is necessary to create effective working relationships, improve cooperation between village officials, and support improved performance and quality of service to the community.